Filtering Firewalls Using Untangle for Network Security Systems at Berlin Computer - Heru Eko Saputro; Khairil Khairil; Hari Aspriyono (GATOTKACA Journal (Teknik Sipil, Informatika, Mesin dan Arsitektur), 2021)
The purpose of this study is to create an expert system application that can be used to diagnose diseases caused by the coxsackie virus in children using the certainty factor method. Viral infectious disease is a collection of types of diseases caused by viruses that easily attack children. Diseases that often occur in children are caused by very vulnerable viruses, this is because the immune system in the child's body has not been fully developed. One of the viruses that often attack children, among others, is the Coxsackie Virus. Coxsackie is a type of disease caused by the Coxsackie virus, which is a type of RNA virus. This virus is transmitted through the fecal oral route, namely bacteria from feces or feces that move from one person to another and enter the mouth of the other person. This system is designed using PHP Programming Language and MySQL Database. With this expert system, it is easier for users to consult about diseases caused by the Coxsackie Virus in children.